Tradisi Peletakan Poster Ayat Al-Quran Pada Rumah Makan Di Sampit Provinsi Kalimantan Tengah - Lukman Hakim; Ahmad Fauziannur (Syntax Idea)
This article begins with an interesting phenomenon that the author found, namely that almost all restaurants located in the rest area around the Trans Kalimantan road that connects Kotawaringin Timur district and Palangaka Raya City, have a unique tradition, namely placing verses of the Koran in the walls of the restaurant which in this case is part of the study living Qur'an. From the research findings, it is known that the living Qur'an, which is carried out by restaurant owners placing verses of the Qur'an, is a form of transcendental communication to Allah SWT. Where by placing the verses of the Qur'an, the owner of the restaurant hopes that Allah SWT can bestow His grace and protection on the family and place of business they have. The Living Qur'an is also carried out as an affirmation of the self-identity of the restaurant owners as Muslim, with the aim that visitors know about it and can help visitors get food that is halal and good to eat.